Determinants of ESG (Environment, Social and Governance) and CFP (Corporate Financial Performance) for Brazilian public companies - Barroso, João Luis Tenreiro (2024)
Multilateral organizations and society in general increasingly demand a corporate posture that maximizes business returns, but considering environmental, social and governance aspects. What has come to be known as ESG (Environmental, Social and Governance) is becoming highly relevant in academic literature and in the corporate world. Despite the widespread support for this type of practices, there is still no consensus regarding the consequences it brings to the financial performance of companies (CFP). The objective of this thesis is to analyze the association of ESG performance scores with the characteristics of Brazilian public listed companies, as well as evaluate if there is correlation of those scores with different measures of Corporate Financial Performance. This work aims contribute for the debate of sustainability and analyze evidence that could enrich the still scarce existing studies of this field for emerging countries, especially in Brazil. Analyzing public companies composing IBOVESPA from 2015 to 2022 and using data from Bloomberg and nefin (FEA-USP), we estimated a fixed effects multiple regression model with panel data through different strategies. Evidence show that corporate ESG Scores are significantly and positively associated with some firm’s characteristics like size, leverage, and profitability. These findings could be interpreted as more socially visible organizations, those big, more mature and highly profitable, being committed with sustainability and its disclosure. The indebtedness could have relation with the commonly demanded banking agreement clauses, called covenants, that debtors must comply. These findings are consistent with most previous studies on the subject, and with the Stakeholder Theory and the Legitimacy Theory which associates sustainable corporate performance and its disclosure with firms with higher financial results. The negative association with tangibility comes mainly from the governance pillar. On the other hand, big firms with high EBITDA margins and liquid shares perform very well in this governance dimension. We have also found a positive and statistically significant association of corporate ESG Score with measures of CFP, like the stocks “excess return” - using traditional and multifactor models –, taken the risk constant, what might reveal that the stock’s market is valuing sustainable firms’ securities. The positive correlation of both Return on Assets (ROA) and Return on Invested Capital (ROI) with Social ESG pillar score could come through increase in productivity and competitive advantages brought by human resources policies, product and service innovation and reputation. These results are in line with most of those found in the literature which reveal a positive association of financial and non-financial corporate performance, confirming the Stakeholder Theory in this universe. Tobin’s q, like a great part of previous studies, has no statistical association with ESG performance in both directions, at least in the short run. This work brings conclusions that could be relevant for corporate executives, institutional investors, asset managers, fund raisers, researchers, and policy makers.